Scent.byreen / Azhanis Azreen Mohd Azhan - Mohd Azhan, Azhanis Azreen (2021)
The social media portfolio is for Principles of Entrepreneurship subject requirement. The project involved promoting and marketing business through Facebook page. Student required to find a suitable product for their business and sell them through Facebook page. However, students must start and register the Go-Ecommerce as evidence that student already sign up for their registration before running the business through Facebook page. Next, the requirement of this social media portfolio is the Facebook page must achieve the total likes exceed 91 likes. For my business, I have chosen to sell a perfume from Victoria secret which my business name called @Scent.byreen. The reason why I named it as a @Scent.byreen because I sell perfume that have a variety of scent and combination with my nickname which is Reen. There are a several type and scent that Scent.byreen sell. The price also affordable for all ages even they are a student, a worker or an elder. There are many types of scent that suits everyone so customer can freely choose the scent according to their taste and their personality. Our perfume is suits both genders not only focus on a woman, man also can wear our perfume. Scent.byreen is always come with a many type of promotion, our promotion of free postage is always for an early bird and promotion will come whenever there is a special date for our business such as Birthday Sale in honor of the owner’s birthday. Our price range is from RM 25 until RM 50 which is very cheap and affordable to all customers. Unfortunately, in the middle of my posting I am facing the challenge where my first account Facebook page which is @Victoriasecret.rn has been reported by somebody and my account was disable. After that, I have created the new account which is my current account and continue make a posting of teaser, hard sell and soft sell.